1996
DOI: 10.1002/(sici)1521-186x(1996)17:3<246::aid-bem11>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Effect on the immune system of mice exposed chronically to 50 Hz amplitude-modulated 2.45 GHz microwaves

Abstract: The effect of continuous (CW; 2.45 GHz carrier frequency) or amplitude‐modulated (AM; 50 Hz square wave) microwave radiation on the immune response was tested. CW exposures (6 days, 3 h/day) induced elevations of the number of antibody‐producing cells in the spleen of male Balb/c mice (+37%). AM microwave exposure induced elevation of the spleen index (+15%) and antibody‐producing cell number (+55%) in the spleen of male mice. No changes were observed in female mice. It is concluded that both types of exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Epidemiological studies have suggested that residential and occupational exposure to ELF are linked to cancer incidence, especially leukemias (Thurston and Saffer 1995;Juutilainen et al 1990) and male breast cancer (Demers et al 1991). Moreover, important effects on endocrine and immune systems have been described (Elekers et al 1996;Graham et al 1996Graham et al , 2000aSemaoui 1996;Stevens et al 1996), and another possible target of ELF is cardiac rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have suggested that residential and occupational exposure to ELF are linked to cancer incidence, especially leukemias (Thurston and Saffer 1995;Juutilainen et al 1990) and male breast cancer (Demers et al 1991). Moreover, important effects on endocrine and immune systems have been described (Elekers et al 1996;Graham et al 1996Graham et al , 2000aSemaoui 1996;Stevens et al 1996), and another possible target of ELF is cardiac rhythm.…”
Section: Introductionmentioning
confidence: 99%